Knowledge and Attitude Towards Premarital Sex among Senior Secondary School Students in Ikorodu Central, Lagos State - Kehinde Alao; Olaitan Balogun; Possible Popoola; Oluwafisayomi Olowu; Jacqueline Aboh; Gloria Olaniran (Nursing and Health Sciences Journal (NHSJ), 2024)
Sex is a close physical act between two individuals which includes genital contact. It usually refers to the characteristics and traits of biological sex. In Nigeria, a number of studies have shown that sexual activity among youth is not only high but on the rise. It is based on this premise that the researcher investigates the knowledge and attitude towards premarital sex among senior secondary school students in Ikorodu central, Lagos state. Descriptive research design of correlation type was adopted for the study. (240) public senior secondary school students in Ikorodu Central Local Government Area of Lagos State were selected through a multistage sampling technique. A self-developed questionnaire was used for data collection. The data collected was analyzed using descriptive statistics of frequency count, percentage, mean and standard deviation, as well as inferential statistics of independent sample t-test at significance level of 0.05. The findings of the study have shown that there is a high level of knowledge of premarital sex among the respondents and most of the respondents have negative attitude towards pre-marital sex. The results indicate that there is no significant gender disparity in attitude towards premarital sex among secondary school students in Ikorodu. The study therefore recommended the need for comprehensive sex education programs tailored to address misconceptions and negative attitudes towards premarital sex among adolescents, thus promoting healthier decision-making and behaviours in this crucial demographic group.